Australian constitutional landmarks / edited by H.P. Lee, George Winterton. - Lee, H. P., 1947-; Winterton, George, 1946- (Cambridge University Press, 2003)
Australian Constitutional Landmarks presents the most significant cases and controversies in the Australian constitutional landscape up to its original publication in 2003. Including the Communist Party case, the dismissal of the Whitlam government, the Free Speech cases, a discussion of the race power, the Lionel Murphy saga, and the Tasmanian Dam case, this book highlights turning points in the shaping of the Australian nation since Federation. Each chapter clearly examines the legal and political context leading to the case or controversy and the impact on later constitutional reform. With contributions by leading constitutional lawyers and judges, as well as two former chief justices, this book will appeal to members of the judiciary, lawyers, political scientists, historians and people with a general interest in Australian politics, government and history.